2015
DOI: 10.4103/0300-1652.149172
|View full text |Cite
|
Sign up to set email alerts
|

Application of sigma metrics for the assessment of quality control in clinical chemistry laboratory in Ghana: A pilot study

Abstract: Background:Sigma metrics provide a uniquely defined scale with which we can assess the performance of a laboratory. The objective of this study was to assess the internal quality control (QC) in the clinical chemistry laboratory of the University of Cape Cost Hospital (UCC) using the six sigma metrics application.Materials and Methods:We used commercial control serum [normal (L1) and pathological (L2)] for validation of quality control. Metabolites (glucose, urea, and creatinine), lipids [triglycerides (TG), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…Sigma metric analysis is used to measure the performance of a process [8]. In clinical laboratories, assessment of the performance can be done separately for preanlytical, post analytical and analytical phases or as overall laboratory process system.…”
Section: Resultsmentioning
confidence: 99%
“…Sigma metric analysis is used to measure the performance of a process [8]. In clinical laboratories, assessment of the performance can be done separately for preanlytical, post analytical and analytical phases or as overall laboratory process system.…”
Section: Resultsmentioning
confidence: 99%
“…In many Chinese clinical laboratories, the Westgard multiplication rules (1 3s , 2 2s , R 4s , 4 1s , 10 x ) have been widely used in clinical chemistry. In this method, there may be more false rejection, waste of quality control materials and prolonged test awaiting time (TAT), whereas the sigma metrics approach allows a laboratory to take a broader view of the data, joining estimates of bias and imprecision into a practical judgment on the clinical usefulness of the method's quality control criteria . Thus, it is useful and simple to access and choose optimal internal quality control criteria based on sigma metrics.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory settings, the former purpose is fulfilled by total allowable error (TEa) and bias whereas coefficient of variation (CV) can be utilized for the later. Several studies have addressed analytical performance of biochemical parameters on sigma scale . Literature review revealed a lack of studies assessing the analytical performance of hematological parameters on sigma scale.…”
Section: Introductionmentioning
confidence: 99%